Pengaruh Produksi, Konsumsi, Harga Eceran, Inflasi Dan Kurs Dollar As Terhadap Impor Gula Indonesia - Eka Saputa, I Kadek; Yogiswara, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Control the import of thisis necessary so that as not to damagethe economy, one of which is the objectof this study was imported sugar. Ifimports too much thendomestic production could not competeand can damage themarket price. This study intended to determine whether there is a significant relationshipbetween production, consumption, retail prices, inflation and the U.S. dollarexchange rate on sugar imports of Indonesia from 2000 to 2012. Techniques ofanalysis in this study using multiple linear analysis, F-test for simultaneoustesting and t-test for partial testing. The results of data analysis showedsimultaneous production, consumption, retail prices, inflation and the U.S.dollar exchange rate significantly influence the Indonesian Sugar Imports2000-2012 period, with a coefficient of determination R2 of0.932 means 93.2 percent variable production, consumption, retail prices,inflation and the U.S. dollar exchange rate affect the Indonesian Sugar Imports2000-2012 period and other variables that affect the remaining 6.8 percent arenot included in the research model. Partially negative and significantproduction, consumption and a significant positive effect, retail prices,inflation and the U.S. dollar exchange rate did not significantly influence theIndonesian Sugar Imports 2000-2012 period.
Keywords: sugar imports; production; consumption; retail prices; inflation; the U.S. dollar exchangerate